A Critical Discourse Analysis of Mother-Child Relationships in Little Fires Everywhere: The Influence of Race and Social Class - Farihah, Inasa Hana; Handayani, Lucia Lusi Ani (ppjbsip, 2024)
Since the Great Migration in 1910, millions of African-Americans moved to Northern, Western, and Midwestern cities, prompting White flight to the suburbs in search of a racially homogeneous utopia. These suburban areas, rooted in discrimination, have a history of systemic racism. Little Fires Everywhere (2020), a Hulu mini-series based on Celeste Ng’s novel, explores these dynamics in a Midwestern suburb. Previous studies have linked race and class to motherhood in the series, revealing that racism often intertwines with structural disparities between ethnic groups. This paper examines the mother-daughter conflicts in Little Fires Everywhere, arguing that these conflicts arise not only from racial structures but also from the specific societal norms of suburban life. Using Fairclough’s (1989) three-dimensional Critical Discourse Analysis (CDA) model, this study uncovers the ideologies embedded in dialogue, the power relations produced through language, and how these elements shape relationships. The analysis reveals that racial identities and social class significantly impact mother-daughter dynamics. The Richardsons’ conservative, upper-class status fosters a superficial and strained relationship, while the Warrens’ financial struggles lead to dissatisfaction and dishonesty. The study highlights how language in the series reflects and reinforces power dynamics, influencing the characters’ relationships.